From 'screen time' to the digital level of analysis: protocol for a scoping review of digital media use in children and adolescents. Issue 11 (25th November 2019) - Browne, Dillon Thomas; May, Shealyn; Hurst-Della Pietra, Pamela; Christakis, Dimitri; Asamoah, Tracy; Hale, Lauren; Delrahim-Howlett, Katia; Emond, Jennifer A; Fiks, Alexander G; Madigan, Sheri; Prime, Heather; Perlman, Greg; et al.
Abstract : Introduction: Research on the relationship between digital media exposure and child development is complex, inconsistent and fraught with debate. A highlighted area of inadequacy surrounds the methodological limitations of measuring digital media use for both researchers and clinicians, alike. This protocol aims to (1) identify core concepts in the area of screen time and digital media use in children and adolescents (2) map existing research paradigms and screening/measurement tools that serve to underpin and operationalise core concepts and (3) provide an initial step in integrating these findings into a consolidated screening toolkit. It is expected this enterprise will help advance research and clinical evaluation in fields concerned with digital media use, namely medicine, child development and the social sciences. Methods and analysis: The planned scoping review will search relevant electronic databases, including Ovid MEDLINE, PsycINFO and Scopus, in addition to grey literature. All empirical investigations and presentation of original research will be considered, and measurement/screening tools for digital media usage in children and adolescents will be identified and reported on. Two reviewers will pilot test the screening criteria, and data extraction forms prior to independently screening all relevant literature and extracting the data. A three-stage synthesis process will be used to map the existent measurement and screening tools for digital media usage in children and adolescents. Ethics and dissemination: There are no ethical considerations for this scoping review. Plans for dissemination include publication in a top-tier, open-access journal, public presentations and conference proceedings. Presentation of the full scoping review has been accepted to the American Academy of Child & Adolescent Psychiatry 66th Annual Meeting.